Effectiveness of Bench Top Non-Vacuum Autoclaves on Dental Turbine Chamber Sterilization Effectiveness of Bench Top Non-Vacuum Autoclaves on Dental Turbine Chamber Sterilization - Taraneh Movahhed; Behjatalmolook Ajami; Mahboobe Dehghani; Ehsan Kiamanesh; Kiarash Kiarash; Nazila Ariaee (Journal of Dental Materials and Techniques, 2013)
Introduction: Dental turbine chamber is a suitable reservoir for living microorganisms, so chamber sterilization is necessary for reducing cross contamination risk. On the other hand, in non-vacuum autoclaves, steam penetration into turbine chamber is doubtful, while they are still in use in dental clinics. In this study, performance of small non-vacuum autoclave in turbine chamber sterilization was evaluated. Methods: A total of 48 dental turbines were sterilized by large vacuum autoclaves. The turbin chamber cap was opened in aseptic enviroment and a strip contaminated with bacillus stearothermophilus endospores was placed into chamber and chamber cap was closed. Twelve dental turbines were loaded in each of four autoclaves (2 large pre-vacuum autoclaves, 2 bench top non-vacuum autoclaves) and sterilization process preformed according to the manufacturer's instructions. After the sterilization cycle, the strips were transferred to culture medium and incubated at 56°C for 48 Hours. As control sample, a biologic indicator that had not been autoclaved was used for each group. Results: Being loaded in different autoclaves, All 48 turbines were sterilized properly and all the cultures were negative. The culture results of four control indicators which were not sterilized, were positive. Conclusion: There was no difference between performance of vacuum and non-vacuum autoclaves in dental turbine chamber sterilization. Both types performed sterilization properly.